THE USE OF THINK PAIR SHARE TECHNIQUE IN TEACHING SPEAKING - Yunita Khusnul Aeni (IKIP Siliwangi, 2020)
The aim of this research was to describe the use of Think Pair Share technique in teaching speaking at the eighth grade of a Junior High School in Bandung. Think Pair Share is a part of cooperative learning strategies that enables the students work together in a small group. The research was conducted using qualitative research method involving 25 students as the research subjects. The data were gathered from observation and questionnaire. The result of the data analysis indicated that the students’ experience after they were taught by using Think Pair Share has shown their excitement towards the teaching process as described. There are good implications in speaking performance after learning by Think Pair Share technique. Think Pair Share technique in this case can be one of the alternative teaching techniques used by the English teacher in teaching English, especially speaking. Keywords: Speaking, Think Pair Share